End group tuning in small molecule donors for non-fullerene organic solar cells. (April 2020) - Guo, Jie; Balakirev, Dmitry O.; Gu, Chengjun; Peregudova, Svetlana M.; Ponomarenko, Sergei A.; Liu, Zhitian; Luponosov, Yuriy N.; Min, Jie; Lei, Aiwen
Abstract: Two novel small molecules, which consist of electron donating benzodithiophene core bridged through bithiophene π-spacer with terminal either dicyanovinyl (DCV-Me) or n- butyl cyanoester (CNAB) electron-withdrawing groups, were designed and used as donor materials for all-small molecule OSCs (all-SM-OSCs) with a non-fullerene acceptor (IDIC). The novel donor oligomers were firstly characterized by thermal gravimetric analysis, differential scanning calorimetry, UV–Vis spectroscopy, and cyclic voltammetry as well as studied by density functional theory calculations. The simple change of the DCV-Me to CNAB group leads to more pronounced crystallinity, higher solubility and higher energy levels in the donor BDT-2T-CNAB . The photovoltaic devices based on the BDT-2T-CNAB:IDIC blend exhibit higher short-circuit current ( J sc ) and fill factor, and thus much higher power conversion efficiency (PCE) of 6.17% than those of BDT-2T-DCV-Me:IDIC devices (1.56%). Compared to the BDT-2T-DCV-Me system, the BDT-2T-CNAB based device shows smoother film surface morphology, and superior exciton dissociation, charge generation and charge carrier mobilities as well as lower non-geminate recombination losses. The results clearly demonstrate that the design of new small molecule donors for high-performance all-SM-OSCs should aim to choose suitable end acceptor units, among which the alkyl cyanoester groups are one of the most promising. Graphical abstract: Image 1 Highlights: Small molecule donors with dicyanovinyl (BDT-2T- DCV-Me ) or n -butyl cyanoester (BDT-2T- CNAB ) groups are reported. BDT-2T-D CV-Me :IDIC and BDT-2T- CNAB :IDIC based OSCs showed PCEs of 1.56% and 6.17%, respectively. BDT-2T- CNAB system exhibits better morphology and charge cariery mobility than BDT-2T- DCV-Me one.